(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
The landscape established during social isolation for the prevention of contagion from COVID-19reveals the aggravation (or ironic metaphor) of a project of enclosing the bodies and the sensitivity that occurs since the beginning of colonization in Brazil and here, inspired by the ideas of Luiz Antônio Simas and Luiz Rufino, I present as a process of disenchantment. In this paper I share the paths trodden with the students of the Degree in Theater of UDESC, discipline of Mask Theatre - fully remotely attended - in which we’ve used the home space, the screens, the materials available in that context and the main pillars of the masks language as creation devices, not only to be aware of the course summary - and as an act of resistance - , but also to find gaps in the metaphorical prison and produce life and enchantment.